TECHNOLOGY INTEGRATION AND COLLABORATIVE LEARNING: DRIVING THE 21ST CENTURY TRANSFORMATION OF HIGHER EDUCATION - Hemi Pamuraharjo; Kardi Kardi; Nawang Kalbuana (CV. ADIBA AISHA AMIRA, 2024)
This research aims to explore and analyze the central issues faced in the integration of technology and collaborative learning in transforming higher education in the 21st century. The research method used is literature review. The findings in this study confirm that technology integration and collaborative learning have great potential in supporting the transformation of higher education, but there are several barriers that need to be overcome. First, the gap in access to technology is still evident among students from various economic and geographical backgrounds. Second, the issue of digital literacy among educators and students, which often does not keep pace with the technological advancements used in learning, requires more intensive and sustainable training programs. Third, data security and privacy issues that arise with the use of digital platforms, requiring stronger policy frameworks and more effective implementation of security technologies. Fourth, challenges in the design of effective assessments to measure collaborative learning outcomes and integrated technologies. This research suggests increased access to technology, better digital literacy training, stronger privacy policies, and the development of new assessment methods as key steps to optimize learning